Multiscale methods in computational mechanics progress and accomplishments - Borst, René de.; Ramm, E. (Ekkehard) 1940-.; SpringerLink (Online service). (Dordrecht Springer, 2011)
Many features in the behaviour of structures, materials and flows are caused by phenomena that occur at one to several scales below common levels of observation. Multiscale methods account for this scale dependence: They either derive properties at the level of observation by repeated numerical homogenization of more fundamental physical properties defined several scales below (upscaling), or they devise concurrent schemes where those parts of the domain that are of interest are computed with a higher resolution than parts that are of less interest or where the solution is varying only slowly. This work is a result of a sustained German-Dutch cooperation and written by internationally leading experts in the field and gives a modern, up-to-date account of recent developments in computational multiscale mechanics. Both upscaling and concurrent computing methodologies are addressed for a range of application areas in computational solid and fluid mechanics: Scale transitions in materials, turbulence in fluid-structure interaction problems, multiscale/multilevel optimization, multiscale poromechanics.
Content: Part 1: Computational Fluid Dynamics: Residual-based Variational Multiscale Theory of LES Turbulence Modeling, by Y. Bazilevs, V.M. Calo, T.J.R. Hughes, and G. Scovazzi -- A Posteriori Error Estimation for Computational Fluid Dynamics. The Variational Multiscale Approach, by G. Hauke, M.H. Doweidar, and D. Fuster -- Advances in Variational Multiscale Methods for Turbulent Flows, by P. Gamnitzer, V. Gravemeier, and W.A. Wall -- Variational Germano Approach for Multiscale Formulation, by I. Akkerman, S.J. Hulshoff, K.G. van der Zee, and R. de Borst -- Dissipative Structure and Long Term Behavior of a Finite Element Approximation of Incompressible Flows with Numerical Subgrid Scale Modeling, by R. Codina, J. Principe, and S. Badia -- Large-eddy Simulation of Multiscale Particle Dynamics at High Volume Concentration in Turbulent Channel Flow, by B.J. Geurts -- Part 2: Materials with Microstructure, An Incremental Strategy for Modeling Laminate Microstructures in Finite Plasticity ? Energy Reduction, Laminate Orientation and Cyclic Behavior, by K. Hackl, and D.M. Kochmann -- The Micromorphic vs. Phase Field Approach to Gradient Plasticity and Damage with Application to Cracking in Metal Single Crystals, by O. Aslan, and S. Forest -- Homogenization and Multiscaling of Granular Media for Different Microscopic Constraints, by C. Miehe, J. Dettmar, and D. Zäh -- Effective Hydraulic and Mechanical Properties of Heterogeneous Media with Interfaces, by L. Dormieux, L. Jeannin, and J. Sanahuja -- An Extended Finite Element Method for the Analysis of Submicron Heat Transfer Phenomena, by P. Lee, R. Yang, and K. Maute -- Part 3: Composites, Laminates and Structures -- Optimization: Multiscale Modeling and Simulation of Composite Materials and Structures, by J. Fish -- Multiscale Modelling of the Failure Behavior of Fibre-reinforced Laminates, by M.V. Cid Alfaro, A.S.J. Suiker, and R. de Borst -- Improved Multiscale Computational Strategies for Delamination, by O. Allix, P. Gosselet, and P. Kerfriden -- Damage Propagation in Composites ? Multiscale Modeling and Optimization, by E. Ramm, A. Erhart, T. Hettich, I. Bruss, F. Hilchenbach, and J. Kato -- Computational Multiscale Model for NATM Tunnels: Micromechanics-Supported Hybrid Analyses, by S. Scheiner, B. Pichler, C. Hellmich, and H.A. Mang -- Optimization of Corrugated Paperboard under Local and Global Buckling Constraints, by T. Flatscher, T. Daxner, D.H. Pahr, and F.G. Rammerstorfer -- Framework for Multi-Level Optimization of Complex Systems, by A. de Wit, and F. van Keulen -- Part 4: Coupled Problems and Porous Media: A Multiscale/Multiphysics Model for Concrete, by B.A. Schrefler, F. Pesavento, and D. Gawin -- Swelling Phenomena in Electro-Chemically Active Hydrated Porous Media, by W. Ehlers, B. Markert, and A. Acartürk -- Propagating Cracks in Saturated Ionized Porous Media, by F. Kraaijeveld, and J.M. Huyghe.
Electronic reproduction.
Keywords: Mechanics -- Data processing; Mechanics, Analytic -- Mathematics; Multiscale modeling; Electronic books